THE IMPLEMENTATION OF MASLAHAH IN THE LOAN OR REVOLVING FUND FINANCING PROGRAM BY LPDB-KUMKM - Anam, Syaiful; R. Suhaimi (Universitas Muhammadiyah Surabaya, 2024)
This research aims to delve into the implementation of the concept of maslahah in the revolving fund loan or financing program managed by the Cooperatives, Micro, Small, and Medium Enterprises Revolving Fund Management Agency (LPDB-KUMKM). The research method employed is a literature review with a descriptive qualitative approach. Secondary data was obtained from various sources, including journals, relevant research, and books related to the research context. The results of the research indicate that LPDB-KUMKM has overall implemented the maslahah concept in its programs. This finding is reflected in several aspects. Firstly, LPDB-KUMKM has successfully fostered economic self-reliance for its cooperative and MSME partners through fund provision, training, and mentoring. Secondly, the institution ensures that all implemented programs adhere to the characteristics of Sharia compliance by avoiding elements of usury, ambiguity, and gambling. Thirdly, the institution conducts a comprehensive risk evaluation, encompassing credit risk, operational risk, and compliance risk. The fourth, LPDB-KUMKM actively engages in community empowerment through training programs, mentoring, and providing access to other resources. The fifth aspect encompasses LPDB-KUMKM's commitment to accountability and transparency at every stage of revolving fund management. Finally, the institution actively participates in an ongoing evaluation and improvement process to ensure the efficiency and effectiveness of the implemented programs.